2022
DOI: 10.1002/ldr.4148
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and compost amendments alter the structure of the soil fungal network in a karst mountainous area

Abstract: The karst ecosystem is prone to degradation and this accounts for a large proportion of land degradation in southwestern China. In order to improve the nutrient status and microbial community structure of karst soil, the amendment method of combining biochar, compost, and chemical fertilizer l was explored. With CK as the control, M as manure compost, B as wood biochar, and F as chemical fertilizer, field trials were set up with eight treatments. The results showed that the biochar treatments led to higher fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…At the same time of the pot experiment, we also carried out a field experiment of similar treatments in the karst mountain area of Guizhou (from 2016 to 2018). By analyzing the soil nutrient content and soil microbial community characteristics and other indicators, combined with a pot experiment, we found that the 4% biochar + MF treatment can play an important role in local soil health and vegetation restoration [4,28,56,57]. These data provide a scientific and theoretical basis for the development of biomass energy in karst areas of China.…”
Section: Discussionmentioning
confidence: 76%
“…At the same time of the pot experiment, we also carried out a field experiment of similar treatments in the karst mountain area of Guizhou (from 2016 to 2018). By analyzing the soil nutrient content and soil microbial community characteristics and other indicators, combined with a pot experiment, we found that the 4% biochar + MF treatment can play an important role in local soil health and vegetation restoration [4,28,56,57]. These data provide a scientific and theoretical basis for the development of biomass energy in karst areas of China.…”
Section: Discussionmentioning
confidence: 76%
“…Meanwhile, the chemical properties of soil could affect the microbial community, and soil microorganisms would also affect its physical and chemical properties. Yan et al [17,18] confirmed that the increase in soil nutrient content could promote fungal diversity after biochar addition; correspondingly, the arbuscular mycorrhizal fungal (AMF) community composition was significantly impacted by soil chemical properties, such as TC, TN, TP, and AP. And it was found that the root microorganisms of S. salsa have a negative correlation with soil salinity and nutrients [19].…”
Section: Introductionmentioning
confidence: 99%
“…(2021) found that biochar could also indirectly affect the soil microbial activity, abundance, and diversity through nutrient uptake or improvement of soil properties. Furthermore, some studies similarly showed that the abundance of soil fungal communities increased with the increase of biochar application, and the effect of biochar on soil microbial diversity was closely related to the timing of biochar application ( Yao et al., 2017 ; Yan et al., 2022 ). Dong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2021) found that biochar could also indirectly affect the soil microbial activity, abundance, and diversity through nutrient uptake or improvement of soil properties. Furthermore, some studies similarly showed that the abundance of soil fungal communities increased with the increase of biochar application, and the effect of biochar on soil microbial diversity was closely related to the timing of biochar application (Yao et al, 2017;Yan et al, 2022). Dong et al (2017) and Mitchell et al (2015) showed that the soil microbial community structure did not change when a small amount of biochar was applied to the soil, but it changed significantly when the amount of biochar reached a certain level, indicating that the amount of biochar applied also had a significant effect on the soil microbial community structure.…”
Section: Introductionmentioning
confidence: 99%